1987
DOI: 10.1080/07315724.1987.10720179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linoleic and oleic acids on blood pressure, blood viscosity, and erythrocyte cation transport.

Abstract: It has been proposed that dietary linoleic acid lowers blood pressure (BP) by being converted to arachidonic acid and prostanoids of the two-ene series. We tested the effects of linoleic acid on plasma arachidonic acid, blood pressure, blood viscosity, and RBC cation transport. Oleic acid, the major dietary monounsaturated fat and which is not a prostanoid precursor, was used as a control. Seventeen adults consumed 23 g/d of linoleic acid or oleic acid provided by genetic variants of safflower seed, each for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…In addition, we have observed that diet supplementation with oleic and linoleic acid did not reveal changes in this transport system. 27 On the basis of these findings, we conclude that dietary manipulations do not affect RBC Li + -Na + countertransport.…”
Section: Genetic Factors and Rbc LImentioning
confidence: 85%
“…In addition, we have observed that diet supplementation with oleic and linoleic acid did not reveal changes in this transport system. 27 On the basis of these findings, we conclude that dietary manipulations do not affect RBC Li + -Na + countertransport.…”
Section: Genetic Factors and Rbc LImentioning
confidence: 85%
“…[26][27][28][29] In contrast to these findings, several studies have failed to show an effect on BP by increased intake of linoleic acid. 5,[30][31][32][33] In two studies with study periods of 6-8 months, a reduction of BP was observed during a low-fat, high-fibre diet 34 and an American Heart Association Step I diet with moderate fat reduction and equal amounts of SAFA and PUFA. 35 Trials with n-3 fatty acids have indicated that very high intakes of fatty fish and supplementation with fish oil concentrates decrease both SBP and diastolic BP (DBP).…”
Section: Introductionmentioning
confidence: 99%
“…Son impact est principalement étudié dans le cadre des maladies cardiovasculaires, de la régulation des LDL plasmatiques, de leur contenu en cholestérol et de leur oxydabilité [3], éventuellement lors d'un traitement hypocalorique [4]. Il intervient aussi dans la modulation de la pression et de la viscosité sanguines et, enfin, du transport des cations dans les érythrocytes [5]. L'acide oléique pourrait contribuer à un bon contrôle de l'hypertriglycéridémie chez le rat diabétique [6], il potentialise l'effet de la perte de poids qui diminue le risque cardiovasculaire chez les patients obèses et diabétiques [7].…”
Section: Discussionunclassified